The Transformative Potential of Inquiry: Engaging With and Navigating Complex “Worlds” - Carolin Kreber (Teaching & Learning Inquiry: The ISSOTL Journal)
I propose a model of the scholarship of teaching and learning that builds on and at the same time extends previous work. This article revisits the idea of inquiry as a collaborative social practice enriched by critical reflection and critical self-reflection on assumptions, making a case that among the various functions of inquiry (e.g., increasing effectiveness, enhancing understanding, etc.) is an important emancipatory one, which plays out on two levels: it fosters personal development and agency, but may also lead to social change in our institutions and wider society. This is the transformative potential of inquiry. Looking forward, I make two points: First, I suggest that through inquiry into genuine problems both students and academics not only come to know more, they are also changed in fundamental ways allowing them to better navigate their increasingly complex worlds. These complex worlds include the “big world” that we all inhabit and seek to better understand through our academic endeavours (learning and inquiring through our fields of study) and the “smaller world” of teaching in higher education. Both worlds are rife with “wicked problems” inviting multiple possible meanings depending on assumed viewpoint, thereby defying straight-forward definitions, analyses, interpretations, and solutions. Second, to fully reach its emancipatory potential, inquiry into these two complex worlds must be grounded in a “situational ethos” that recognizes the needs and challenges of the larger world.